A Patient with Altered Sensorium and Splenic Abscess Diagnosed to Be a Case of Myeloproliferative Disease: A Case Report - Verma, Jyoti; Upendra, Dr. Upendra; Singh, Dr. Indrajeet; Tejaswani, Dr. Tejaswani; Sahu, Sumit sahu (International Journal of Innovative Research in Medical Science, 2024)
About 1.0 to 2.5 individuals per 100000 have essential thrombocytosis every year. The prevalence was seen mostly in females and was reported to be 38 to 57 per 100000 between 2008 and 2010. The incidence increases with age and most of the patients presents in age group of 50 and 60. A middle-aged male patient came with the complain of dragging sensation due to massive splenomegaly without any constitutional symptoms except that there was acute onset of altered sensorium since 1 day. Ultrasound was suggestive of massive splenomegaly with splenic abscess. Later he was diagnosed to be the case of hematological disorder i.e Myeloproliferative disorder.